La mediación familiar : algunas consideraciones - Darriba Fraga, Guillermo (Revista de Derecho de la UNED (RDUNED), 2010)
Taking into account basic premises such as the creation of new family entities and the citizens’ awareness of the fact that, in a democratic system with inalienable values and principles such as the respect of human dignity, the resolution of interrelational problems, specially those which affect the most intimate sphere, can be, and are perfectly undertaken, overcome and solved without the need of state guardianship; the author makes an approach to family mediation as a procedure, encouraged today but not always with a fortunate approach by the different legislative powers. Family mediation not only gives a breath of fresh air to the ways of directing and solving conflicts but also satisfies the urgent need in the reform of the Administration of Justice, as well as satisfying a citizens’ right and duty to become directly involved in the social life assuming the responsibilities of composing their disputes.